Characteristic morphological and syntactic features of English in Kenya: a corpus study (ice) - Budohoska, Natalia (Lingua Posnaniensis, 2012)
This study discusses characteristic morphological and syntactic features of English in Kenya on the basis of the International Corpus of English (ICE) for Kenya. It contains a list of typical traits compiled following the universal criteria for describing varieties of English set up by Kortmann (2008: xxv-xxix). The features found were confronted with the Szmrecsanyi & Kortmann (2009: 68) concept of the inherent simplification of the new varieties of English. Finally, the amount of variation found in the ICE was placed into a wider context of other postcolonial varieties of English. The results of this analysis add to the discussion of recognizing English in Kenya as an emancipated variety of English (Budohoska 2011a, b). This study presents a high degree of characteristic features of English in Kenya, many of them shared with other recognized varieties of English. It also reveals tendencies of simplification common to New Englishes. The estimated frequencies of these features, however, are too low to reveal stigmatized forms of Kenyan English.